Penerapan Aplikasi Pemetaan Cabang Bank XXX Berbasis Android Menggunakan Metode Grounded Research - Achmad Faisal; Halimatusa'diah; Irnawati Irnawati (Jurnal Publikasi Teknik Informatika, 2025)
The development of information and communication technology today has driven significant changes in the banking industry, including in terms of customer service. One innovation that can improve customer experience is an Android-based bank branch mapping application, which allows users to easily find the nearest branch or ATM location. This study aims to develop an Android-based Bank XXX branch mapping application using the Grounded Research method. This method was chosen because it can dig up a deep understanding of user needs and preferences through direct data collection from the field.